1978
DOI: 10.1113/jphysiol.1978.sp012173
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition of the mammary secretion of women after abrupt termination of breast feeding.

Abstract: 1. The composition of mammary secretion has been followed in seven women before and after abrupt termination of breast feeding. The period of full lactation was 39 days for 1 woman and a mean of 332 days (range 251--443 days) for the six others. Small samples of mammary secretion (0.5--5.00 ml.) were collected by manual expression from three women at monthly intervals throughout 12 months of lactation and from seven women at frequent intervals for 42 days of involution. 2. During full lactation (12 months, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…Indeed, in studies of bovine lactation, serum albumin in milk has been used as a marker of mammary integrity (Schanbacher & Smith, 1975) and its concentration is increased during mastitis. Evidence from human studies that the albumin concentration of milk is increased at the cessation of lactation is consistent with this (Hartmann & Kulski, 1978).…”
Section: Introductionsupporting
confidence: 66%
“…Indeed, in studies of bovine lactation, serum albumin in milk has been used as a marker of mammary integrity (Schanbacher & Smith, 1975) and its concentration is increased during mastitis. Evidence from human studies that the albumin concentration of milk is increased at the cessation of lactation is consistent with this (Hartmann & Kulski, 1978).…”
Section: Introductionsupporting
confidence: 66%
“…These results confirm the findings of Ramadan et al (1972), except that these authors observed a decrease in the total protein content of the milk which they attributed to a reduction in the levels of casein in the milk. However., the results from their investigation may have been complicated by changes in the milk composition associated with involution of the gland (Hartmann and Kulski, 1978), as suckling was not permitted from the inflamed breast. In the present study involutionary changes were avoided because the baby was normally suckled from the inflamed breast.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on human lactation have shown very little variation in the milk composition during established lactation (Macy, 1949;Hartmann & Kulski, 1978). In each of these studies the milk was sampled at weekly or monthly intervals.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that during established lactation in women the concentrations of lactose and the ions in breast milk remain relatively stable (Macy, 1949;Hartmann & Kulski, 1978). Furthermore, the negative correlations between the concentrations of lactose and the ions in breast milk during this time suggest that these constituents are transported from the secretary cells into milk by the transcellular P. E. HARTMANN AND C. G. PROSSER pathway (Peaker, 1976).…”
Section: Introductionmentioning
confidence: 99%